Alterations in the proximal nephron of beige mice with the Chédiak-Higashi syndrome. - Eguchi, M. (1982)
The proximal nephron of C57 beige mice with a genetic defect analagous to the Chédiak-Higashi syndrome (CHS) has been compared with that of normal C57 black mice. The concanavalin A-horseradish peroxidase (Con A-HRP) technique stained the brush border of the proximal straight tubule heavily in black mice and weakly in beige mice. In beige mice this method stained the brush border of the proximal convoluted tubules weakly and the brush border of the proximal straight tubules only negligibly. Periodic acid-Schiff staining showed no such difference between beige and black mice but revealed an increase distally in the size of the CHS inclusions in the proximal straight tubule of beige mice. Immunostaining visualized abundant lysozyme in the first portion of the proximal nephron but none in the more distal segments of beige and black mice alike. At the ultrastructural level, the proximal convoluted tubules of black mice contained two morphologic types of heterophagosomes, which apparently differed in accord with the stage of their development. Proximal straight tubules contained morphologically different heterophagic bodies. The mature stages of these heterophagosomes were greatly enlarged in CHS mice. With the periodic acid-thiocarbohydrazide-silver proteinate (PA-T-SP) method for localizing glycoprotein ultrastructurally, the microvillar brush border, apical invaginations of the plasmalemma, Golgi cisternae, and lysosomal inclusions stained selectively in the proximal nephron in both strains. The proximal straight nephron of beige mice after staining with the PA-T-SP method appeared depleted of the strongly reactive apical invaginations in some areas, particularly where large heterophagosomes bordered the apical plasmalemma. The enlarged secondary lysosomes of heterophagic origin in beige mice varied in showing both diffuse and focal PA-T-SP reactivity. Lysosomal acid phosphatase activity appeared decreased, and peroxisomes were normal in size but increased in number in the proximal nephron of beige mice.